Pregnancy complicated by refractory severe hypercholanaemia from sodium taurocholate co‐transporting polypeptide deficiency. Issue 2 (10th November 2020) - Wu, Christine; Smet, Maria‐Elisabeth; Heath, Susan; Curnow, Jennifer; Lin, Ming‐Wei; George, Jacob; Alahakoon, Thushari I.
Abstract: Sodium taurocholate co‐transporting polypeptide deficiency is a rare metabolic autosomal recessive condition resulting in critically elevated plasma bile acid levels. Hypercholanaemia in similar conditions such as intrahepatic cholestasis of pregnancy has been associated with an increased risk of adverse obstetric outcomes including stillbirth. We present the first case of Sodium taurocholate co‐transporting polypeptide deficiency in a current pregnancy in a patient with one previous stillbirth in the context of severe hypercholanaemia, where conventional treatments for cholestasis including ursodeoxycholic acid, rifampicin and cholestyramine were ineffective. Therapeutic plasma exchange and novel treatment with elobixibat were trialed with mixed results. The pregnancy resulted in an iatrogenic preterm delivery of a live infant at 32 weeks gestation.